Instrumentos de mensuração do clima escolar: análise crítica - Meguerditchian, Alan Ary (2024)
The scientific community, both nationally and internationally, has devoted itself to measuring the so-called school climate. As it has been identified in meta-analyzes as a relevant factor for both student learning and other factors in the school educational process, this knowledge production has focused on developing various scales and conducting empirical studies. At the same time, the systematic reviews identified the great complexity of the school climate concept and the low comparability as problems. In this sense, this research proposed to contribute through the development of a content analysis protocol applied to the two most used instruments in Brazilian studies, as shown in a bibliographic review of theses and dissertations from 2013 to 2023: GEPEM (VINHA et al., 2017) and the adapted Delaware School Climate Survey Student (DSCS-S) instrument, (HOLST, 2015). With this, supported by Critical Theory, we sought to understand the nature, content, and treatment of the facts of school life dynamics about which subjects are asked to respond by examining the items. In this way, it was possible to make the items of the constructs comparable and to overcome the analysis between the explanations of the concepts and their dimensions, which were found to be ineffective according to the literature review. The starting point was the hypothesis that while the instruments share common features, they also share structural divergences that could coexist if the pedagogical visions guiding these instruments were explained, but which ultimately lead to a fragmentation of the field and generate a low level of comparability if not made explicit. In addition, the absence of essential aspects of social relations in Brazilian schools weakens the instruments' ability to capture the tensions existing in classroom units and generate the notion of the normality of interactions and the efficiency of school institutions. The hypotheses were confirmed and it was added that the identification of items with unifying and standardizing characteristics is relevant – especially when the questionnaires deal with aspects and practices of an institutional and formal nature. Therefore, the protocol was found to be appropriate and can be used to analyze other instruments, allowing the comparison of a larger number of constructs